The Effect of Independence Education in Islamic Boarding School on the Development of Emotional Intelligence of Elementary School Students - Lia Pratiwi; Tati Nurhayati; Patimah Patimah; Nur Atikoh (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis study was intended to determine the effect of independence education in Islamic boarding schools on the development of emotional intelligence in Qur’ani Islamic Elementary School of Al-Bahjah Cirebon. This research is a quantitative research using the post facto method. The data collection techniques used were observation sheets, questionnaire sheets, and documentation. The research data were analyzed using the determination test. Based on the test of the effect of independence education in Islamic boarding schools on the development of emotional intelligence, this study showed 57.1%, meaning that there is an effect of independence education in Islamic boarding school environment on emotional intelligence of students Qur’ani Islamic elementary school of Al-Bahjah Cirebon while the rest is influenced by other factors. Thus, it is expected that independence education in the boarding school environment can become a role model in the application of independence education in all formal educational institutions so that the children of Indonesia become independent generations who have high emotional intelligence.Keywords: self-reliance, emotional intelligence, Islamic boarding schools. AbstrakTujuan penelitian ini adalah untuk mengetahui pengaruh pendidikan kemandirian di pondok pesantren terhadap perkembangan kecerdasan emosional siswa Sekolah Dasar Islam Qur’ani (SDIQu) Al-Bahjah Cirebon. Jenis penelitian ini yaitu penelitian kuantitatif menggunakan metode expost facto. Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi, angket, dan dokumentasi. Data hasil penelitian dianalisis melalui uji determinasi. Berdasarkan uji determinasi pengaruh pendidikan kemandirian di pondok pesantren terhadap perkembangan kecerdasan emosional dalam penelitian ini menunjukkan 57,1%, artinya terdapat pengaruh pendidikan kemandirian di lingkungan pondok pesantren terhadap kecerdasan emosional siswa SDIQu Al-Bahjah Cirebon. Sedangkan sisanya dipengaruhi oleh faktor lain. Dengan demikian, diharapkan pendidikan kemandirian di lingkungan pondok pesantren dapat menjadi role model dalam penerapan pendidikan kemandirian di seluruh lembaga pendidikan formal agar anak-anak bangsa Indonesia menjadi generasi mandiri yang memiliki kecerdasan emosional yang tinggi.Kata kunci: kemandirian, kecerdasan emosional, pondok pesantren.